Caspase-dependent apoptotic mechanism of gallic acid and its derivatives isolated from quercus infectoria ethyl acetate extract against cervical cancer cells lines (hela) - Ismail, Illyana (2023)
Cervical cancer is one of the most common cancers in women worldwide. In 2020, cervical cancer ranked the fourth most diagnosed cancer among Malaysian women. The induction of apoptosis is one of the essential mechanisms to prevent the process of carcinogenesis. The previous study indicated that natural products were able to induce apoptosis and showed promising advantages in cancer treatment. The Quercus infectoria galls (QI) have been reported to have antimicrobial, antioxidant, anticancer and wound healing activities. However, the antiproliferative activity and the underlying molecular mechanisms against human cancer cells have been poorly elucidated. Hence, the present study was undertaken to examine the cell death mechanisms of gallic acid and its derivatives isolated from Quercus infectoria ethyl acetate extract (EAQI) against cervical cancer cells (HeLa). Gallic acid (GA) and its derivative, methyl gallate (MG), were isolated by using a bioassay-guided isolation technique. The antiproliferative effect that characterised by inhibitory concentration at 50 % cell populations (IC50) of EAQI, GA and MG were determined by using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide] assay at various concentration ranging from 0.39 to 100 μg/ml at 72 hours of treatment in HeLa cell lines and the control serving non-cancerous Vero cell lines. Cisplatin was used as a positive control, while untreated HeLa and Vero cells served as the negative control. Changes in cell morphology were measured by acridine orange/propidium iodide (AO/PI) staining for 24, 48 and 72 h. Viable, apoptotic and necrotic cells were identified using a fluorescence microscope. Determination of phosphatidylserine (PS) externalisation was performed using annexin-V Fluorescein isothiocyanate (FITC) / propidium iodide (PI) dual staining assay. The cells were treated for 3, 6 and 12 h and analysed by flow cytometry. Cellular deoxyribonucleic acid (DNA) content was measured in HeLa cells using flow cytometry at 24, 48 and 72 h for cell cycle distribution. Apoptosis pathways were elucidated based on pro and anti-apoptotic protein expressions (p53, Bax and Bcl-2) at 3 hours of treatment and caspases activity (caspase-8 and -9) were analysed by flow cytometry technique at 6 hours of treatment. The results showed that EAQI, MG and GA exhibited the antiproliferative effect on HeLa cells with IC50 values of 11.50 ± 0.5 μg/ml, 11.00 ± 0.58 μg/ml and 10.00 ± 0.67 μg/ml, respectively. In the cell morphology analysis, cells treated with IC50 value of EAQI, MG and GA displayed an increased apoptotic cell population compared to untreated cells (p<0.05) at 72 hours of treatment. The induction of apoptosis was confirmed by the externalisation of phosphatidylserine on early apoptotic cells, which showed the treated cell population shifted from viable to apoptotic quadrant. Based on the cell cycle distribution, the accumulation of cells at the subG0 phase in treated cells indicated the discontinuity of deoxyribonucleic acid DNA fragmentation and led to apoptosis. Furthermore, the results showed that p53 and Bax (pro-apoptotic proteins) were expressed in the treated cells, whereas Bcl-2 (anti-apoptotic protein) was not expressed at 3 hours of treatment. The caspase analysis also revealed that EAQI, MG and GA had induced apoptosis by activating caspase-8 and -9 at 6 hours of treatment. In conclusion, these findings suggested that EAQI, MG and GA significantly induced apoptotic mechanisms via the regulation of intrinsic and extrinsic pathways, which should provide new insight into therapeutic activity and anticancer agents of QI.